Effect of defoliation and miner damage on the quality and production of Gypsophila paniculata L. - TORRES, ALEXANDER; ACOSTA, ALFREDO; ASTAIZA, RODRIGO (Revista Colombiana de Entomología, 1995)
In order to quantify the decrease in quality and production of G. paniculata, the difference between the mechanical leaf running and the leafminer Liriomyza huidobrensis (Blanchard) damage was evaluated. Two trials were conducted to compare the defoliation against the damage produced by two leafminer populations. The first trial was conducted in Madrid (Cundinamarca) at 2.600 masks. Four levels of defoliation (0,25, 50, and 75%) were evaluated at four crop stages: 1, 5, 9, and 13 weeks. In the second trial, in Santafé de Bogotá, three leafminer adult densities were evaluated: O, 0.7, and 1.3 adults per leaf of Gypsophila at the same four crop stages. The defoliation did not affect the production severely, when it occurred only once at any crop stage, decreasing only 22% with a 75% defoliation on the 9th week. This is the most susceptible crop stage to leaf loss. The defoliation of 25% in week 13th increased production by 13,8%. Any defoliation at weeks 1 and 5 retarded the harvest between 6 and 12 days, without affecting the flower quality. In the second trial, the densities of 0.7 adults per leaf on week 5th and 1.3 on week 9th decreased production in 38 and 46.7% respectively. The leafminer did not decrease the production on week 13th, but when the attack ocurred during the first week it retarded, from 15 to 20 days, the beginning of the harvest. The flower and stem biomass were affected by the leafminer on weeks 5 and 9.